Effect of zinc on immune recovery in HIV patients. Medellín 2013. Randomized controlled trial - Contreras Martínez, Heidy Johanna; Duque Molina, Marcela Maria; Vásquez Trespalacios, Elsa Maria; Sanchez Garzon, Juliana (CES Medicina, 2017)
Introduction: The human immunodeficiency virus (HIV) infection progressively destroys the immune system and increases the susceptibility to opportunistic infections. The aim of this study was to assess the benefits and safety of zinc supplements at nutritional doses. Methods: A randomized, double-blind, placebo control trial was performed in 40 adult patients that received either zinc sulfate or placebo daily during 12 weeks. The CD4 lymphocytes count was evaluated at the beginning and at the end of the intervention. Furthermore, we evaluated different clinical and epidemiological variables. Results: After the intervention, an increase ≥ 20% in CD4 lymphocytes was compared between groups; better response was observed in patients who received zinc (90% vs. 25%, p = 0.00), RR = 3.6 (95% CI 1.66; 7.8, p = 0.000) and reduction of relative risk of 74% compared to placebo. Conclusion: This clinical trial shows that patients who receive zinc sulfate supplement could increase the CD4 lymphocyte counting.